MODELOS PARENTALES EN EL SURESTE DE MÉXICO, EL CASO DE LA ZONA DE LA CHONTALPA EN TABASCO, MÉXICO - Marín Turriza, Juana; Ferrer Córdova, Euler (Gênero & Direito, 2020)
This paper aims to present a study of parental models in fathers and mothers, considering this institution as the space where economic, politic and social transformations produced by the social dynamics are reflected in several ways. The concept of parental models is understood as the set of norms and rules that regulate behaviors (breeding patterns), model of communications based on the time of coexistence and the ways tos how affection (links of attachment), and the promotion of guidelines linked to success (success patterns), aspects explored with the Atribucional Questionnaire on Parental Models (Martìnez et al., 2014), applied to 1900 families from the five municipalities that make up the Chontalpa region of the State of Tabasco. The study reveals that parents use negotiating and rigid breeding patterns, warm and close ties of attachment and patterns success counselors and promoters.